Beyond pity and inspiration a critical discourse analysis on the representation of children with disabilities in Maalaala mo Kaya - Buensuceso, Era Cassandra Valdez; Ilagan, Cecile Angela A. (Quezon City College of Mass Communication, University of the Philippines, 2023)
This study examined the representation of children with disabilities (CWDs) in the Philippine TV drama anthology program, Maalaala Mo Kaya (MMK). Utilizing the framework of Critical Discourse Analysis (CDA) and Critical Disability Theory (CDT), the study aimed to problematize the construction of disability in the media and explore the societal influences and power dynamics shaping these representations. Applying the principles of CDT, the study sought to understand how societal constructions and power dynamics influence disability portrayals at the textual, discursive and social levels of discourse practice. The findings highlighted both outdated and nuanced representations of disability among CWDs, revealing discursive practices that either reinforced or challenged ableist norms within MMK. One notable finding was the prevalence of portraying disability as a divine punishment, shedding light on the religious inclinations of Filipinos. This research contributes to the understanding of disability representations in local media and advocates for inclusivity and the empowerment of CWDs.

KEYWORDS: children with disabilities, representation, media, discourse, power dynamics, intersectionality
Sinuri ng pag-aaral na ito ang representasyon sa mga batang may kapansanan sa programa sa telebisyon na Maalaala Mo Kaya (MMK). Gamit ang teoretikong balangkas ng Critical Discourse Analysis (CDA) at Critical Disability Theory (CDT), siniyasat ng pag-aaral ang konstruksyon ng midya sa nosyon ng kapansanan at galugarin ang impluwensiyang panlipunan at power dynamics na nakapaloob sa iba't ibang antas ng teksto, discursive practice at sosyal na talastasan. Natuklasan ng pag-aaral ang pagkakaroon ng mga outdated at nuanced na representasyon ng kapansanan sa palabas. Isa sa mga mahalagang natuklasan sa pagsusuri ng teksto ay ang malimit na paglalarawan ng kapansanan bilang parusa mula sa langit, isang pagpapatunay sa relihiyosong kultura ng mga Pilipino. Layunin ng pananaliksik na mag-ambag sa mas maim na pang-unawa sa diskurso at representasyon ng midya tungkol sa mga batang may kapansanan at magtulak ng pagtataguyod ng kanilang karapatan sa lipunan.
Vita.
Thesis
Includes bibliographical references (pages 135-147) and appendices (pages 148-161).
Keywords: People with disabilities in mass media .